PERAN UNIT PELAKSANA TEKNIS DAERAH PERLINDUNGAN PEREMPUAN DAN ANAK (UPTD PPA) KABUPATEN SIDOARJO DALAM MENANGANI KEKERASAN TERHADAP ANAK - Tri Prasetijowati; Fierda Nurany; Sarah Ayundasari Rudhito (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
This study used qualitative research methods. The role of the UPTD PPA as a regulator is the existence of rules and regulations related to the protection of victims and underlies protection activities with the issuance of Regional Regulation of Sidoarjo Regency Number 18 of 2006 2015 concerning the protection of women and children victims of violence. The role of the UPTD PPA as a facilitator is the availability of facilities, infrastructure, and human resources that support the process of handling victims of violence. The role of the UPTD PPA as executor itself, namely complaint services, health rehabilitation, social rehabilitation, to the return of victims to their environment. The role of UPTD PPA as a coordinator is to network and coordinate with various related parties, such as OPD, LSM, and the community itself. Then the inhibiting factors are clients or victims who don't want to be open, limited human resources. And the efforts made by the UPTD PPA in dealing with violence against children are by socializing and increasing the competence of their human resources